Teaching English Concrete Nouns Using Pictionary Game - Miftah Nur Jannah (Universitas PGRI Adi Buana Surabaya, 2016)
The study discusses the effectiveness of teaching Englishconcrete noun using Pictionary game. The background of the studyis based on the phenomena that students in SDN Sendangrejo IIINgimbang usually get bored to learn vocabulary especially onconcrete nouns. That is the reason why the teacher should device agood exercise or a way of teaching English concrete nouns.Learning vocabulary at Elementary School can be done throughmany ways, so the researcher teaches vocabulary using Pictionarygame. This game may become an alternative way to teach Englishnouns for beginning level. It is more emphasizing on activelearning and language teaching, because it makes students moreactive. The purpose of the study is to know whether or not usingPictionary game is effective to improve students’ English concretenouns in the fourth graders of SDN Sendangrejo III Ngimbang.This study is categorized as a quantitative research. The data isobtained by giving test to the experimental class and control classafter giving a different learning to both classes. The number of thesubjects is twenty in each class. They are IV A is as experimentalclass, and IV B control class. The instruments used to collect thedata were documentation and test. Test was used to know students’competence before and after the experiment run. There are twokinds of test. They are pre-test and post test. The result of theresearch showed that the use of Pictionary game as a media ofteaching concrete nouns was effective. There was a significancedifference in the achievement between students in class IV A(experimental class) and students in class IV B (control class). It isshowed of the mean of experimental class is higher than controlclass (80.70 > 73.35). On the other hand, the test of hypothesisusing t-test formula shows the value of the t-test is higher than thevalue of the t-table. The value is (3.141>1.68). The hypothesis isaccepted. Therefore it can be concluded that the use of Pictionarygame as a media of teaching concrete nouns was effective.